STRATEGI PEMERINTAH DALAM MENINGKATKAN PENGEMBANGAN PARIWISATA DI KABUPATEN BOLAAANG MONGONDOW UTARA - ROBINSON, TRIVAN KING; KIYAI, BURHANUDDIN; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of research is to know the government's strategy in improving tourism development in NorthBolaang Mongondow district. The study uses qualitative approach methods. The informant is the head oftourism Department of 1 person, head of section 3 persons, staff/officers of Tourism Office 4 persons,community/Tourist 7 people so total informant there are 15 persons. Data collection using interviewguidelines, while the analytical techniques used are interactive model analyses of Miles and Hubernan.Based on the results of the research that has been done by the authors, it can be concluded as follows: Itcan be drawn some conclusions as follows: (1) SO strategy (Strength and opportunities) using theappropriate promotional media target according to the market that will be addressed by the tourism agencyso that the right target and continue to be done will intensively produce excellent results. Innovate andexplore more types and destinations of tourism objects offered and committed to provide the best service toconsumers to maintain the good image of tourism in the eyes of consumers. (2) The strategy of ST (strengthand treats) Bolmut Regency government can offer interesting and promising new things with thepresentation of quality of natural resources and the interesting tour. Related to changes in the price andtariff charged can be informed through the means of promotion and description of tourist attractions in themedia and Disarana and facilities in the attraction. Do not forget to also increase other innovations relatedto tourism such as creativity in the manufacture of OLE-ole or fruit. (3) The strategy of WO (weakness andopportunities) to ensure that the tariff or charges on similar tourism objects will be the way to overcome theexisting threats. In addition, the training and education provider to the community related to tourismmanagement is also very needed. Do not forget to add facilities and supporting facility and recycle orrerejuvenation existing facilities and amenities to make it look more attractive. (4) The strategy of WT(weakness and treats) enhances the safety and comfort of tourists who come to visit. To establish competitiveprice but not detrimental for tourism and community office. Care and maintenance must be routinely runon every attractionKeywords: Strategy, Government, Tourism Development